CONTENT ANALYSIS OF ENGLISH TEXTBOOK “INTERACTIVE ENGLISH” USED IN FIRST GRADE JUNIORHIGH SCHOOL IN 2013 CURRICULUM - Monica Septiani Tambunan (JETAL: Journal of English Teaching & Applied Linguistic, 2019)
The objectives of this study are to find out the suitability of impressionistic and in-depth analysis in the textbook entitles "Interactive English” used for the seventh grade of Junior High School. This research is conducted by applying descriptive qualitative. The data was collected by documenting the content materials on the textbook and it was analyzed by using Cunningsworth's theory. The result showed that an English textbook entitle “Interactive English" fulfilled the criteria proposed in Cunningsworth's theory concerning the impressionistic textbook analysis with score 96% and in-depth textbook analysis with the summative score 87%. From those summative scores, the textbook was categorized as a good enough textbook and suitable enough to use as media in teaching and learning process. [W81]Rata kanan dan kiri harus sesuai dengan tubuh artikel